Systematic review and meta‐analysis of patient race/ethnicity, socioeconomics, and quality for adult type 2 diabetes. (27th July 2020) - Lee, Woolton; Lloyd, Jennifer T.; Giuriceo, Katherine; Day, Timothy; Shrank, William; Rajkumar, Rahul
Abstract: Objective: To review the evidence of the association between performance in eight indicators of diabetes care and a patient's race/ethnicity and socioeconomic characteristics. Data Source: Studies of adult patients with type 2 diabetes in MEDLINE published between January 1, 2000, and December 31, 2018. Study Design: Systematic review and meta‐analysis of regression‐based studies including race/ethnicity and income or education as explanatory variables. Meta‐analysis was used to quantify differences in performance associated with patient race/ethnicity or socioeconomic characteristics. The systematic review was used to identify potential mechanisms of disparities. Data Collection: Two coauthors separately conducted abstract screening, study exclusions, data extraction, and scoring of retained studies. Estimates in retained studies were extracted and, where applicable, were standardized and converted to odds ratios and standard errors. Principal Findings: Performance in intermediate outcomes and process measures frequently exhibited differences by race/ethnicity even after adjustment for socioeconomic, lifestyle, and health factors. Meta‐analyses showed black patients had lower odds of HbA1c and blood pressure (BP) control (OR range: 0.67‐0.68, P < .05) but higher odds of receiving eye or foot examination (OR range: 1.22‐1.47, P < .05) relative to white patients. A high school degree or more was associated with higher odds of HbA1c control and receipt of eye examinations compared to patients without a degree. Meta‐analyses of income included a handful of studies and were inconsistently associated with diabetes care performance. Differences in diabetes performance appear to be related to access‐related factors such as uninsurance or lacking a usual source of care; food insecurity and trade‐offs at very low incomes; and lower adherence among younger and healthier diabetes patients. Conclusions: Patient race/ethnicity and education were associated with differences in diabetes quality measures. Depending on the approach used to rate providers, not adjusting for these patient characteristics may penalize or reward providers based on the populations they serve.